Methodological approaches to shoreline assessment: short-term analysis of beach erosion rates - Baptista, Paulo (2012)
Determination of accurate short-term coastal erosion rates in sandy shores require special care in what concerns: (1) shoreline indicator field feature definition and identification, (2) technological approach to position the adopted shoreline indicator and methodologies used for data gathering; (3) and computational procedures to measure shoreline retreat between surveying epochs. When all these aspects are considered it is possible to filter out the noise, which can be related with random errors introduced during the data acquisition process, and compute reliable beach erosion rates from short-term studies (pluri-annual). Results can provide a powerful tool for coastal scientists, coastal engineers and coastal managers.